Preliminary evaluation of pomegranate peel extracts for the control of Rhizopus rot of stone fruits - Taberner, Verónica; Pérez-Gago, María B.; Palou, Lluís (2025)
Rhizopus or soft rot caused by Rhizopus stolonifer is one of the most important postharvest diseases of stone fruits, potentially causing nests of decay and significant economic losses. Natural plant extracts such as those from pomegranate (Punica granatum L.) fruit peels can exert antifungal activity, mainly due to their high polyphenol content. Fruit peels and membranes can be obtained in large amounts as by-products of the pomegranate processing industry. The objective of this work was to preliminarily assess the ability of two ‘Mollar de Elche’ pomegranate peel extracts (PPE), a methanolic PPE and an aqueous PPE, to control soft rot on ‘Big Bang’ and ‘Carmina’ nectarines and ‘Angeleno’ plums. For this, each fruit was artificially inoculated once in a peel wound with a spore suspension of R. stolonifer and, 2 h later (assessment of curative activity), 30 μL of PPE were applied in the same wound with a micropipette. After 7 days of incubation at 20 ºC, the application of methanolic PPE (30 g/L) reduced the incidence of Rhizopus rot (number of infected wounds) by 58, 28, and 63% and the Rhizopus rot severity index (RRSI, scale 0-4 where 0 = 0%, 1 = 1-25%, 2 = 26-50%, 3 = 51-75%, and 4 = 76-100% of decayed fruit surface) by 82, 56, and 57%, compared to the control treatment (30 μL of water), on the cultivars ‘Big Bang’, ‘Carmina’, and ‘Angeleno’, respectively. Aqueous PPE (30 g/L) was less effective, with disease incidence reductions of 21, 31, and 24% and RRSI reductions of 61, 53, and 24%, respectively. In conclusion, ‘Mollar de Elche’ PPEs could be promising sustainable postharvest treatments to be included within non-polluting integrated disease management (NPIDM) strategies for the control of soft rot of stone fruits. Furthermore, the valorization of pomegranate by-products can greatly contribute to circular bioeconomy as well to the EU Green Deal and the UN Sustainable Development Goals.